2011
DOI: 10.1186/1471-2318-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Long-term declines in ADLs, IADLs, and mobility among older Medicare beneficiaries

Abstract: BackgroundMost prior studies have focused on short-term (≤ 2 years) functional declines. But those studies cannot address aging effects inasmuch as all participants have aged the same amount. Therefore, the authors studied the extent of long-term functional decline in older Medicare beneficiaries who were followed for varying time lengths, and the authors also identified the risk factors associated with those declines.MethodsThe analytic sample included 5,871 self- or proxy-respondents who had complete baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 35 publications
6
51
1
Order By: Relevance
“…These variables were included because (1) the claims experience of persons in managed care would be different than those in fee-for-service (under-represented), and (2) the assessments of change in function and health are affected by whom (self-respondent vs. proxy respondent) is answering the survey questions. 18 …”
Section: Methodsmentioning
confidence: 99%
“…These variables were included because (1) the claims experience of persons in managed care would be different than those in fee-for-service (under-represented), and (2) the assessments of change in function and health are affected by whom (self-respondent vs. proxy respondent) is answering the survey questions. 18 …”
Section: Methodsmentioning
confidence: 99%
“…We also adjust for two health behaviors, smoking and regular exercise. Epidemiological studies have shown that adults who smoke are at increased risk of disability whereas those who exercise regularly have a reduced risk (d'Orsi et al, 2014; Hardy, McGurl, Studenski, & Degenholtz, 2010; Wolinsky et al, 2011). Moreover, smoking is predictive of higher circulating levels of inflammatory proteins whereas physical activity is linked to lower levels (Colbert et al, 2004; Jousilahti, Salomaa, Rasi, Vahtera, & Palosuo, 2003; Krabbe, Pedersen, & Bruunsgaard, 2004).…”
mentioning
confidence: 99%
“…Although differences were identified within a country and across China and South Korea, given the nature of this comparative study, the discussion focuses on cross-country differences. By and large, the functional status of East Asian community-dwelling older adults is similar to the functional status of those in Western societies, which are relatively healthy and present few functional limitations (Wolinsky et al, 2011).…”
Section: Discussionmentioning
confidence: 96%